Creation’s Poetics and Musical Foundation in Antonio Gamoneda’s Voice from his “mudanza” of The Flower Songs of Nezahualcoyotl - Aguirre Martínez, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In 2016 Antonio Gamoneda published his translations (“mudanzas”) of some of the poems written by the king-poet Nezahualcoyotl. This paper links Gamoneda's translation experience with one of reanimation of the word. The poet, as a shaman, gives the language its energy back. In other words, he revives it as if it were a living being. This exercise suggests a re-awakening of the melodic properties of the voice as a first step carried out by the translator before reaching the final form of the words. The structure of the following pages will be given by key aspects/terms as cultic function, pharmakon, the nature of the poet or the dialectics between two different models of language.